Systematic Literature Review on the Impact of Land Use and Land Cover (LULC) Pattern on Surface Water Quality: Global Scenario and Bagmati River Basin - Karki, Kamal; Gywali, Saroj; Ghimire, Hari Prasad; Joshi, Hari Prashad (Journal of Engineering Issues and Solutions, 2026)
Land use and land cover (LULC) change represents a critical anthropogenic factor contributing to freshwater degradation, with significant consequences for ecological integrity, human health, and sustainable development. Globally, the expansion of urban settlements, intensification of agricultural practices, and widespread deforestation are strongly correlated with nutrient enrichment, sediment accumulation, and the proliferation of heavy metals and organic contaminants in riverine systems. These dynamics are particularly pronounced in South Asia, with the Bagmati River Basin in Nepal serving as a notable example, where rapid population growth, uncontrolled urbanization, and the absence of adequate wastewater treatment infrastructure have collectively precipitated a severe deterioration of water quality. This systematic literature review (SLR) synthesizes peer-reviewed studies conducted at both global scales and within the Bagmati Basin to assess the mechanisms through which LULC dynamics influence surface water quality. Employing the PRISMA framework, the review evaluates spatial and temporal patterns, methodological approaches, and key drivers of change across more than seventy scholarly contributions. The findings reveal a clear divergence: while the global scientific community has advanced toward integrated hydrological–water quality modeling and the utilization of remote sensing and geospatial analytics, research in the Bagmati Basin remains constrained by fragmented datasets, short study durations, and limited monitoring infrastructure. Despite these divergences, both global and local evidence underscore the urgent need for integrated land and water governance. The review highlights critical gaps in the literature, particularly in elucidating the interactions between LULC dynamics, socioeconomic processes, and climate change drivers in shaping water quality outcomes. Addressing these gaps necessitates interdisciplinary strategies that integrate advanced monitoring systems, coupled modeling frameworks, and robust policy analysis to support evidence-based decision-making. The implications of these findings extend directly to the achievement of the United Nations Sustainable Development Goals, most notably SDG 6 (Clean Water and Sanitation) and SDG 15 (Life on Land).